2019
DOI: 10.3389/fphar.2019.00226
|View full text |Cite
|
Sign up to set email alerts
|

Single and Synergistic Effects of Cannabidiol and Δ-9-Tetrahydrocannabinol on Zebrafish Models of Neuro-Hyperactivity

Abstract: In this study, we aimed to investigate the effect of the two main active cannabinoids extracted from cannabis: Δ-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) on two distinct behavioral models of induced neuro-hyperactivity. We have taken advantage of two previously developed zebrafish models of neuro-hyperactivity: a chemically induced pentylenetetrazole model and a genetic model caused by loss-of-function mutations in the GABA receptor subunit alpha 1 (GABRA1−/−). Both CBD and THC have a significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 47 publications
7
32
0
Order By: Relevance
“…This result is consistent with studies reporting synergistic effects of acute CBD and Δ 9 ‐THC co‐treatment in other animal models of disease including neuropathic pain and epilepsy (Casey et al, 2017; Samarut et al, 2019). Notably, Varvel et al (2006) showed that CBD potentiated the antinociceptive effects of a low 0.3 mg·kg −1 Δ 9 ‐THC dose in mice (Varvel et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with studies reporting synergistic effects of acute CBD and Δ 9 ‐THC co‐treatment in other animal models of disease including neuropathic pain and epilepsy (Casey et al, 2017; Samarut et al, 2019). Notably, Varvel et al (2006) showed that CBD potentiated the antinociceptive effects of a low 0.3 mg·kg −1 Δ 9 ‐THC dose in mice (Varvel et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…We, therefore, examined acute CBD and Δ 9 -THC co-treatment effects on hyperthermiainduced seizures in Scn1a +/− mice and discovered that a subthreshold dose of CBD (12 mgÁkg −1 ) combined with 0.1 mgÁkg −1 THC resulted in a greater anticonvulsant effect than either phytocannabinoid alone. This result is consistent with studies reporting synergistic effects of acute CBD and Δ 9 -THC co-treatment in other animal models of disease including neuropathic pain and epilepsy (Casey et al, 2017;Samarut et al, 2019). Notably, Varvel et al (2006) showed that CBD potentiated the antinociceptive effects of a low 0.3 mgÁkg −1 Δ 9 -THC dose in mice (Varvel et al, 2006).…”
Section: Enhanced Anticonvulsant Effect Of Combined Cbd and δ 9 -Thsupporting
confidence: 89%
See 1 more Smart Citation
“…These properties combined with the ease of large-scale pharmacological screening make larval zebrafish a good model system for investigating drug targets. A recent study 31 , limited only to locomotion assay read-outs in larval zebrafish, reported a synergistic effect of Δ-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) on hyperactive behaviors. Unfortunately, these studies failed to include electrophysiology measures of efficacy and were limited to only these two compounds.…”
Section: Discussionmentioning
confidence: 99%
“…investigating drug targets. A recent study (Samarut et al, 2019), limited only to locomotion assay read-outs in larval zebrafish, reported a synergistic effect of D-9-tetrahydrocannabinol (THC) and CBD on hyperactive behaviors. Unfortunately, these studies failed to include electrophysiology measures and were restricted to these two compounds.…”
mentioning
confidence: 99%